Hyperbola and the angle bisector

Geometry Level 4

Given that hyperbola x 2 y 2 3 = 1 x^2-\dfrac{y^2}{3}=1 has left focus F 1 F_1 and right focus F 2 F_2 . Point P P on the hyperbola is such that F 1 P F 2 = 2 π 3 \angle F_{1}PF_{2}=\dfrac{2 \pi}3 . The angle bisector of F 1 P F 2 \angle F_{1}PF_{2} intersects the x x -axis at point A A .

Find the length of P A PA .

5 5 \dfrac{\sqrt{5}}{5} 3 5 5 \dfrac{3\sqrt{5}}{5} 5 \sqrt{5} 2 5 5 \dfrac{2\sqrt{5}}{5}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Eccentricity of the hyperbola is 1 + 3 = 2 \sqrt {1+3}=2 . So the coordinates of F 1 F_1 and F 2 F_2 are ( 2 , 0 ) (-2,0) and ( 2 , 0 ) (2,0) respectively. Let the coordinates of P P and A A be ( h , k ) (h, k) and ( a , 0 ) (a, 0) respectively. Then slopes of the line segments P F 1 , P F 2 \overline {PF_1}, \overline {PF_2} and P A \overline {PA} are k h + 2 , k h 2 \dfrac{k}{h+2}, \dfrac{k}{h-2} and k h a \dfrac{k}{h-a} respectively. So we have

h 2 k 2 3 = 1 h^2-\dfrac {k^2}{3}=1

tan 2 π 3 = 3 = k h 2 k h + 2 1 + k 2 h 2 4 \tan \dfrac{2π}{3}=-\sqrt 3=\dfrac{\dfrac{k}{h-2}-\dfrac{k}{h+2}}{1+\dfrac{k^2}{h^2-4}}

tan π 3 = 3 = k h a k h + 2 1 + k 2 ( h a ) ( h + 2 ) \tan \dfrac{π}{3}=\sqrt 3=\dfrac{\dfrac{k}{h-a}-\dfrac{k}{h+2}}{1+\dfrac{k^2}{(h-a) (h+2)}} .

From the first two equations we get h = 5 2 , k = 3 2 h=\dfrac{\sqrt 5}{2}, k=\dfrac {\sqrt 3}{2} .

Substituting the values of h h and k k in the third equation we get a = 2 5 a=\dfrac{2}{\sqrt 5} and P A = ( h a ) 2 + k 2 = 2 5 = 2 5 5 |\overline {PA}|=\sqrt {(h-a) ^2+k^2}=\dfrac {2}{\sqrt 5}=\boxed {\dfrac {2\sqrt 5}{5}} .

I did the same thing as you, only difference is I took parametric form of the point, i.e, (sec,1.732tan). My keypad sucks so I had to type approximate value of square root of 3

Kushal Dey - 1 year, 2 months ago
David Vreken
Mar 19, 2020

Let the x x -coordinate of P P be p p . Since P P is on the hyperbola x 2 y 2 3 = 1 x^2 - \frac{y^2}{3} = 1 , its y y -coordinate is 3 p 2 3 \sqrt{3p^2 - 3} .

Let B B be the intersection of the line through P P perpendicular to F 1 F 2 F_1F_2 . Then B F 1 = p + 2 BF_1 = p + 2 , B F 2 = 2 p BF_2 = 2 - p , and B P = 3 p 2 3 BP = \sqrt{3p^2 - 3} , and by the Pythagorean theorem on P B F 1 \triangle PBF_1 and P B F 2 \triangle PBF_2 , P F 1 = ( p + 2 ) 2 + 3 p 2 3 = 2 p + 1 PF_1 = \sqrt{(p + 2)^2 + 3p^2 - 3} = 2p + 1 and P F 2 = ( 2 p ) 2 + 3 p 2 3 = 2 p 1 PF_2 = \sqrt{(2 - p)^2 + 3p^2 - 3} = 2p - 1 .

By the law of cosines on P F 1 F 2 \triangle PF_1F_2 , 4 2 = ( 2 p + 1 ) 2 + ( 2 p 1 ) 2 2 ( 2 p + 1 ) ( 2 p + 1 ) cos 2 π 3 4^2 = (2p + 1)^2 + (2p - 1)^2 - 2(2p + 1)(2p + 1) \cos \frac{2\pi}{3} , which solves to p = 5 2 p = \frac{\sqrt{5}}{2} for p > 0 p > 0 . Therefore, P F 1 = 2 ( 5 2 ) + 1 = 5 + 1 PF_1 = 2(\frac{\sqrt{5}}{2}) + 1 = \sqrt{5} + 1 and P F 2 = 2 ( 5 2 ) 1 = 5 1 PF_2 = 2(\frac{\sqrt{5}}{2}) - 1 = \sqrt{5} - 1 .

The length of an angle bisector d d of a triangle is d 2 = b c a 2 b c ( b + c ) 2 d^2 = bc - \frac{a^2bc}{(b + c)^2} , so P A = ( 5 + 1 ) ( 5 1 ) 4 2 ( 5 + 1 ) ( 5 1 ) ( 5 + 1 + 5 1 ) 2 = 2 5 5 |PA| = \sqrt{(\sqrt{5} + 1)(\sqrt{5} - 1) - \frac{4^2(\sqrt{5} + 1)(\sqrt{5} - 1)}{(\sqrt{5} + 1 + \sqrt{5} - 1)^2}} = \boxed{\frac{2\sqrt{5}}{5}} .

Chew-Seong Cheong
Mar 19, 2020

It should be noted that the angle bisector P A PA of F 1 P F 2 \angle F_1PF_2 is actually tangential to the hyperbola at P P (see note). For hyperbola x 2 a 2 y 2 b 2 = 1 \dfrac {x^2}{a^2} - \dfrac {y^2}{b^2} = 1 , the tangent at P ( x 0 , y 0 ) P(x_0, y_0) is given by x 0 a 2 x y 0 b 2 y = 1 \dfrac {x_0}{a^2}x - \dfrac {y_0}{b^2}y = 1 . For A ( x A , 0 ) A(x_A, 0) , x A = a 2 x 0 \implies x_A =\dfrac {a^2}{x_0} . Then P A = ( x 0 a 2 x 0 ) 2 + y 0 2 |PA| = \sqrt{\left(x_0-\dfrac {a^2}{x_0}\right)^2+y_0^2} .

To find x 0 x_0 and y 0 y_0 , let F 1 ( c , 0 ) F_1(-c,0) and F 2 ( c , 0 ) F_2(c,0) . Then

c + x 0 y 0 + c x 0 y 0 1 c 2 x 0 2 y 0 2 = tan 2 π 3 2 c y 0 y 0 2 c 2 + x 0 2 = 3 2 c y 0 y 0 2 c 2 + a 2 b 2 y 0 2 + a 2 = 3 Putting a = 1 , b = 3 , c = 2 4 3 y 0 2 + 12 y 0 9 3 = 0 y 0 = 3 2 x 0 = 1 + y 0 2 3 = 5 2 P A = ( x 0 1 x 0 ) 2 + y 0 2 = 2 5 5 \begin{aligned} \frac {\frac {c+x_0}y_0 + \frac {c-x_0}y_0}{1-\frac {c^2-x_0^2}{y_0^2}} & = \tan \frac {2\pi}3 \\ \frac {2cy_0}{y_0^2-c^2+x_0^2} & = - \sqrt 3 \\ \frac {2cy_0}{y_0^2 - c^2 + \frac {a^2}{b^2}y_0^2 + a^2} & = - \sqrt 3 & \small \blue{\text{Putting }a=1, b = \sqrt 3, c=2} \\ 4\sqrt 3 y_0^2 + 12y_0 - 9\sqrt 3 & = 0 \\ \implies y_0 & = \frac {\sqrt 3}2 \\ \implies x_0 & = \sqrt{1+\frac {y_0^2}3} = \frac {\sqrt 5}2 \\ \implies |PA| & = \sqrt{\left(x_0-\frac 1{x_0}\right)^2+y_0^2} = \boxed{\frac {2\sqrt 5}5} \end{aligned}


Note: I am not able to come up with a general proof but we can see that when P P is at the vertex ( a , 0 ) (a,0) , F 2 P F 2 = π \angle F_2PF_2 = \pi and the tangent is vertical. And when P ( , ) P(\infty, \infty) , the tangent is parallel to the asymptote.

Kelvin Hong
Mar 27, 2020

Let P ( x , y ) P(x,y) be its coordinate, then we have x 2 y 2 3 = 1 y 2 = 3 x 2 3. x^2-\frac{y^2}3=1\implies y^2=3x^2-3.

Since F 1 P F 2 = 2 π / 3 \angle F_1PF_2=2\pi/3 , using Cosine Law we have 16 = F 1 F 2 2 = P F 1 2 + P F 2 2 2 P F 1 P F 2 cos ( 2 π 3 ) = P F 1 2 + P F 2 2 + P F 1 P F 2 . 16=F_1F_2^2=PF_1^2+PF_2^2-2PF_1\cdot PF_2\cos\bigg(\dfrac{2\pi}3\bigg)=PF_1^2+PF_2^2+PF_1\cdot PF_2.

By P F 1 2 = ( x + 2 ) 2 + y 2 , P F 2 2 = ( x 2 ) 2 + y 2 , PF_1^2=(x+2)^2+y^2, \quad PF_2^2=(x-2)^2+y^2,

we have 16 = ( x + 2 ) 2 + y 2 + ( x 2 ) 2 + y 2 + ( x + 2 ) 2 + y 2 ( x 2 ) 2 + y 2 = 2 x 2 + 8 + 2 y 2 + ( x + 2 ) 2 + 3 x 2 3 ( x 2 ) 2 + 3 x 2 3 = 2 x 2 + 8 + 2 ( 3 x 2 3 ) + 4 x 2 + 4 x + 1 4 x 2 4 x + 1 = 8 x 2 + 2 + ( 2 x + 1 ) ( 2 x 1 ) because x > 1 = 12 x 2 + 1 x = 5 2 . \begin{aligned}16&=(x+2)^2+y^2+(x-2)^2+y^2+\sqrt{(x+2)^2+y^2}\sqrt{(x-2)^2+y^2}\\ &=2x^2+8+2y^2+\sqrt{(x+2)^2+3x^2-3}\sqrt{(x-2)^2+3x^2-3}\\ &=2x^2+8+2(3x^2-3)+\sqrt{4x^2+4x+1}\sqrt{4x^2-4x+1}\\ &=8x^2+2+(2x+1)(2x-1)\quad\text{ because }x>1\\ &=12x^2+1\\ \therefore x&=\dfrac{\sqrt5}2.\end{aligned}

It is pretty lucky that the terms in square root is a perfect square! By apply y 2 = 3 x 2 3 y^2=3x^2-3 we find y = 3 / 2 y=\sqrt3/2 .

From this we find P F 1 = 5 + 1 , P F 2 = 5 1 PF_1=\sqrt 5+1, PF_2=\sqrt5-1 . Since P A PA is the angle bisector of F 1 P F 2 \angle F_1PF_2 , using area argument we find P F 1 P F 2 = A F 1 A F 2 , \dfrac{PF_1}{PF_2}=\dfrac{AF_1}{AF_2},

Using A F 2 AF_2 as the sole variable here, we find A F 2 = 10 2 5 5 AF_2=\dfrac{10-2\sqrt 5}{5} . Therefore the x x -coordinate of A A is 2 10 2 5 5 = 2 5 5 , 2-\dfrac{10-2\sqrt 5}{5}=\dfrac{2\sqrt5}{5},

Using P ( 5 / 2 , 3 / 2 ) , A ( 2 5 / 5 , 0 ) P(\sqrt 5/2, \sqrt3/2), A(2\sqrt5/5, 0) , we get P A = 2 5 5 PA=\boxed{\dfrac{2\sqrt5}{5}} .

Note: This also shows that Δ A P F 2 \Delta APF_2 is equilateral.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...